THE PLACE OF SHAMS TABRIZI’S PHILOSOPHICAL VIEWS IN ISLAMIC PHILOSOPHICAL THOUGHT (American Journal of Research in Humanities and Social Sciences, 2025)
This article examines the philosophical views of Shams Tabrizi and their significance within the broader context of Islamic intellectual and philosophical thought. As a spiritual guide and mentor to Jalal al-Din Rumi, Shams played a crucial role in shaping mystical-philosophical perspectives that bridged metaphysics, ethics, and the inner dimensions of faith. His reflections on the relationship between the soul, love, and divine truth not only influenced Sufi philosophy but also contributed to the development of Islamic philosophical discourse by emphasizing the unity of existence and the transformative power of spiritual experience. The study highlights how Shams Tabrizi’s teachings continue to inspire contemporary interpretations of Islamic philosophy and spirituality.